2020
DOI: 10.1038/s41396-020-00819-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid- and strain-specific factors drive variation in ESBL-plasmid spread in vitro and in vivo

Abstract: Horizontal gene transfer, mediated by conjugative plasmids, is a major driver of the global rise of antibiotic resistance. However, the relative contributions of factors that underlie the spread of plasmids and their roles in conjugation in vivo are unclear. To address this, we investigated the spread of clinical Extended Spectrum Beta-Lactamase (ESBL)-producing plasmids in the absence of antibiotics in vitro and in the mouse intestine. We hypothesised that plasmid properties would be the primary determinants … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 102 publications
(73 reference statements)
1
85
0
Order By: Relevance
“…Conjugative plasmids, which can mediate their own horizontal transmission, are important vectors of horizontal gene transfer in prokaryotes and a key source of microbial genetic diversity. Many conjugative plasmids carry accessory genes, which can confer resistance to heavy metals or antibiotics [1, 2]. Understanding plasmid dynamics is therefore not only important to understanding bacterial ecology and evolution in general, but also to predict the rise of antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugative plasmids, which can mediate their own horizontal transmission, are important vectors of horizontal gene transfer in prokaryotes and a key source of microbial genetic diversity. Many conjugative plasmids carry accessory genes, which can confer resistance to heavy metals or antibiotics [1, 2]. Understanding plasmid dynamics is therefore not only important to understanding bacterial ecology and evolution in general, but also to predict the rise of antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The IncI1-complex are widespread in Enterobacteriaceae and have been reported to be the major driver of AR in Salmonella and E. coli . Our understanding of their mode of transfer and AR evolution have been limited to studies on their prevalence, mating experiments and in vivo challenge with mice 21, 30, 31 . Fischer et al 32 showed that E. coli populations in broiler chickens acquired β-lactam resistance after 4-days old broiler chicks were gavaged with an E. coli strain carrying blaCTX-M-1 on an IncI1 plasmid.…”
Section: Discussionmentioning
confidence: 99%
“…?ES"7(%0"EM".NO:"5)+"E"():&'%(*):" =.,992&4&)%5'8"+5%5"K^".,992&4&)%5'8"?512&"E>! "?0&"():&'%(*):"7&'&"9'&:&)%"()"*) 28 E. coli was the major IncI1 reservoir in broiler chicks. The application of proximityligation method (Hi-C) has improved the assembly of metagenomes and made it possible to detect plasmid-host associations 21 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors play a role in the ability of plasmids to be transferred between bacteria. For instance, incompatibility restriction, host genetics, and strain-specific factors can influence the transfer of plasmids [ 38 , 74 , 75 ]. In this study, we investigated a total of 18 plasmid incompatibility groups in all E. coli isolates.…”
Section: Discussionmentioning
confidence: 99%